PENGARUH FASILITAS KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR IMIGRASI KELAS I TEMPAT PEMERIKSAAN IMIGRASI (TPI) AMBON - Pocerattu V. Alfonso (Jurnal Administrasi Terapan, 2022)
This study aims to examine the effect of work facilities on employee performance at the Immigration Class I Immigration Checkpoint (TPI) Ambon. This research was conducted because based on the results of the initial survey there were several work facilities that had to be replaced or repaired. The data analysis technique used in this research is quantitative analysis using descriptive statistics and simple linear regression. The independent variable of this study is work facilities (X) and the dependent variable is employee performance (Y). The population in this study were employees of the Immigration office, the sample in this study were 51 people. Based on the research results using simple linear analysis, work facilities have a positive but insignificant effect on employee performance with a value of 0.154> 0.05. This is reinforced by the determination test of R square 0.041, which means that 4.1% of employee performance is explained by work facilities while the remaining 95.9% is explained by other variables not in this study. Keywords : Work Facilities, Employee Performance